Cervical Length Screening Versus History-Indicated Cerclage in Women With Prior Early Preterm Birth [08K]. (May 2020) - Grantham, Lindsey; McLaughlin, Eric; Hade, Erinn; Smith, Devin D.; Samuels, Philip; Frey, Heather A.
Abstract : INTRODUCTION: The objective of this study was to compare the rate of recurrent preterm birth (PTB) <37 weeks in women with prior early PTB who underwent history-indicated (HI) cerclage versus cervical length (CL) screening with cerclage when indicated. METHODS: This retrospective cohort study included women with a singleton pregnancy and a prior spontaneous PTB between 16w0d and 27w6d weeks. The primary outcome was PTB <37 weeks; secondary outcomes included PTB <34 and <28 weeks, spontaneous PTB, and NICU admission. Fisher exact tests and Wilcoxon rank-sum tests were used to compare baseline characteristics and in unadjusted analyses of the outcomes. Marginal logistic regression was used to adjust for confounders and account for women with multiple pregnancies during the study period. RESULTS: Among 357 women, 49 (14%) underwent HI cerclage and 308 (86%) underwent CL screening. HI cerclage patients presented to prenatal care earlier, delivered earlier in their prior pregnancies, and were more were more likely to have had a previous cerclage. Only 84 (27%) women who underwent CL screening required cerclage. Of the 49 women with HI cerclage, 26 (53%) had recurrent PTB versus 43% (n=132) in the CL screening group. The odds of PTB were not significantly different between the two groups (aOR 0.92, 95% CI 0.44-1.92, P= .82). Secondary outcomes did not differ significantly. CONCLUSION: Our results support preferential use of cervical screening for most women with prior early PTB, as it may avoid cerclage in 2/3 of women. This information is useful when counseling high-risk patients about management options.